N-Heterocyclic carbene–palladium catalysts for the direct arylation of pyrrole derivatives with aryl chlorides - Özdemir, Ismail (Beilstein-Institut, 2013)
New Pd–NHC complexes have been synthesized and employed for palladium-catalyzed direct arylation of pyrrole derivatives by using electron-deficient aryl chlorides as coupling partners. The desired coupling products were obtained in moderate to good yields by using 1 mol % of these air-stable palladium complexes. This is an advantage compared to the procedures employing air-sensitive phosphines, which have been previously shown to promote the coupling of aryl chlorides with heteroarenes.